Pretreatment mechanism of β-O-4 lignin during phosphoric acid-acetone process based on density functional theory and molecular dynamic simulations - Junjiao, Zhang; Jinqi, Zhu; Changfeng, Lin; Tipeng, Wang; Changqing, Dong; Wu, Qin (International Journal of Agricultural and Biological Engineering, 2016)
Pretreatment mechanism of β-O-4 lignin (Lβ-O-4) during the phosphoric acid-acetone process involves a series of interactions between lignin and solvent molecule (H2O, CH3COCH3 and H3PO4) which lead to the adsorption, solubility and decomposition of lignin. Coniferyl alcohol guaiacyl glycerol (CAGG) with the predominant linkage (β-O-4 ether bond) was chosen as the model β-O-4 lignin (Lβ-O-4) for investigating the detailed pretreatment mechanism based on density functional theory calculations and molecular dynamic simulations. Interactions between β-O-4 lignin and solvent molecules were firstly detected. Only physical interaction occurred between β-O-4 lignin and the solvent molecule. The attractive van der Waals interaction favored CH3COCH3 molecules approaching to Lβ-O-4, showing a compatibility of Lβ-O-4 in CH3COCH3 solution. Furthermore, following the temperature effect on the dynamics processes, larger dynamics calculations and experiments were carried out to reveal the detailed dissolution and precipitation of β-O-4 lignin in various solutions.Keywords: lignin, lignocellulose, biomass, pretreatment, density functional theory (DFT)DOI: 10.3965/j.ijabe.20160902.2212Citation: Zhang J J, Zhu J Q, Lin C F, Wang T P, Dong C Q, Qin W. Pretreatment mechanism of β-O-4 lignin during phosphoric acid-acetone process based on density functional theory and molecular dynamic simulations. Int J Agric & Biol Eng, 2016; 9(2): 127－136.